Optimalisasi Pelayanan Prima Melalui Konsep A6 di Pelabuhan Penyeberangan Torobulu - Ferima Ferima; Maudhy Satyadharma; Muhammad Yazir Jabbar; Hado Hado; Muhamad Rajulan (Journal of Science, Technology, and Innovation, 2026)
This study aims to analyze the optimization of excellent service through the application of the A6 concept to the service system at the Torobulu Ferry Port in the context of public transportation services based on user experience. The study employs a qualitative-descriptive empirical approach through operational observation, in-depth interviews, documentation, and thematic analysis of the dimensions of attitude, ability, attention, appearance, action, and accountability. The results indicate that service quality has shown positive improvements in service attitude, operational technical ability, and service flow management. Major challenges remain in inconsistent service communication during peak periods, limited digitalization of information, a lack of proactive approaches to user needs, and an underdeveloped public satisfaction-based evaluation system. The study also found that service accountability remains administratively oriented and has not been fully integrated with participatory oversight mechanisms. The integration of service technology, the strengthening of an adaptive service culture, and the development of a user-experience-based evaluation system are strategic factors in realizing professional, responsive, transparent, and sustainable ferry services.